Genomewide analysis of bull sperm quality and fertility traits. (23rd August 2016) - Puglisi, R; Gaspa, G; Balduzzi, D; Severgnini, A; Vanni, R; Macciotta, NPP; Galli, A
Contents: Because the priority of AI industry is to identify subfertile bulls, a predictive model that allowed for the prediction of 91% bulls of low fertility was implemented based on seminological (motility) parameters and DNA status assessed both as DNA fragmentation index (DFI) and by TUNEL assay using sperm of 105 Holstein–Friesian bulls (four batches per bull) selected based on in vivo estimated relative conception rates (ERCR). Thereafter, sperm quality and male fertility traits of bulls were explored by GWAS using a high‐density (777K) Illumina chip. After data editing, 85 bulls and 591, 988 SNPs were retained for GWAS. Of 12 SNPs with false discovery rate <0.2, four SNPs located on BTA28 and BTA18 were significantly associated (LD‐adjusted Bonferroni <0.05) with the non‐compensatory sperm parameters DFI and TUNEL. Other SNPs of interest for potential association with TUNEL were found on BTA3, in the same chromosome where associations with non‐compensatory in vivo bull fertility were already reported. Further suggestive SNPs for sperm membrane integrity were located on BTA28, the chromosome where QTL studies previously reported associations with sperm quality traits. Suggestive SNPs for ERCR were found on BTA18 in the vicinity of a site already associated with in vivo bull fertility. Additional SNPs associated with ERCR and sperm kinetic parameters were also identified. In contrast to other, but very few GWAS on fertility traits in bovine spermatozoa, which reported significant SNPs located on BTX, we have not identified SNPs of interest in this sexual chromosome.